Impact of chronic subthalamic high-frequency stimulation on metabolic basal ganglia activity: a 2-deoxyglucose uptake and cytochrome oxidase mRNA study in a macaque model of Parkinson's disease - Meissner, Wassilios; Guigoni, Celine; Cirilli, Laetitia; Garret, Maurice; Bioulac, Bernard H.; Gross, Christian E.; Bezard, Erwan; Benazzouz, Abdelhamid (The European journal of neuroscience, 2007)
The mechanisms of action of high‐frequency stimulation (HFS) of the subthalamic nucleus (STN) remain only partially understood. Hitherto, experimental studies have suggested that STN‐HFS reduces the activity of STN neurons. However, some recent reports have challenged this view, showing that STN‐HFS might also increase the activity of globus pallidus internalis (GPi) neurons that are under strong excitatory drive of the STN. In addition, most results emanate from studies applying acute STN‐HFS, while parkinsonian patients receive chronic stimulation. Thus, the present study was designed to assess the effect of chronic (10 days) STN‐HFS in the 1‐methyl‐4‐phenyl‐1,2,3,6‐tetrahydropyridine (MPTP)‐treated nonhuman primate. For this purpose, 2‐deoxyglucose (2‐DG) uptake, a measure of global synaptic activity, was assessed in the basal ganglia and the motor thalamus after chronic unilateral STN‐HFS. Cytochrome oxidase subunit 1 (COI) mRNA expression, a marker of efferent metabolic activity, was additionally assessed in the globus pallidus. Chronic STN‐HFS (i) reversed abnormally decreased 2‐DG uptake in the STN of parkinsonian nonhuman primates, (ii) reversed abnormally increased 2‐DG accumulation in the GPi while COI mRNA expression was increased, suggesting global activation of GPi neurons, and (iii) reversed abnormally increased 2‐DG uptake in the ventrolateral motor thalamus nucleus. The simultaneous decrease in 2‐DG uptake and increase in COI mRNA expression are difficult to reconcile with the current model of basal ganglia function and suggest that the mechanisms by which STN‐HFS exerts its clinical benefits are more complex than a simple reversal of abnormal activity in the STN and its targets.